Pengembangan Immersive Laboratory Berbasis Virtual Reality Pada Standar Pemeriksaan Kehamilan Dalam Meningkatkan Kualitas Pembelajaran - Pramitasiwi, Putu Devi Angginova; Sindu, I Gede Partha; Wahyuni, Dessy Seri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The development of Information and Communication Technology in the era of Society 5.0 has driven the adoption of educational technologies capable of enhancing learning quality, including in midwifery education. Virtual Reality (VR) offers a potential solution to bridge the gap between theoretical knowledge and practical skills in pregnancy examinations among midwifery students, particularly given the limitations of training models and insufficient opportunities for independent practice. This study aims to analyze the design, implementation, and user experience and response in the development of a VR-based immersive laboratory application for standard pregnancy examinations at the Midwifery Study Program, Faculty of Medicine, Universitas Pendidikan Ganesha. The research employed a Research and Development (R&D) approach using the Multimedia Development Life Cycle (MDLC) model, which consists of the stages of concept, design, material collecting, assembly, testing, and distribution. The development results show that the VR application successfully passed black-box testing with 100% functionality. Product validity testing by content and media experts, which was conducted iteratively (MDLC), yielded a Gregory agreement percentage of 1.00, categorized as “Highly Valid.” User experience evaluation was conducted using the User Experience Questionnaire (UEQ) involving 26 respondents. The results indicated an “Excellent” rating across all aspects, with the highest scores recorded in the Stimulation and Novelty dimensions. This finding indicates that the VR application is highly effective in creating an immersive and independent practice environment, thereby successfully bridging the gap between students' theoretical knowledge and practical skills in pregnancy examinations.